APLIKASI SISTEM PENDUKUNG KEPUTUSAN PENERIMA BANTUAN SOSIAL TUNAI (BST) DENGAN METODE FUZZY TSUKAMOTO - Cut Lutfianda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2020)
The government has issued policies and programs to anticipate the handling of this pandemic, one of which is the Social Assistance Program provided through the leading sector of the Ministry of Social Affairs of the Republic of Indonesia in the form of social assistance programs provided to the poor and communities that have a socio-economic impact from the corona pandemic. One of the programs launched by the government through the Ministry of Social Affairs is the Cash Social Assistance Program or Cash Social Assistance. The research objective was to develop a decision support system application for cash social assistance recipients (BST) with the Tsukamoto fuzzy method which can be used as a tool to quickly determine BST recipients. The several stages of work consist of; data collection, analysis, design and application design, implementation, and testing and evaluation. Based on the results of research and testing of the decision support system to determine BST recipients using the Fuzzy Tsukamoto method that has been carried out by researchers, several conclusions can be drawn, namely: 1) Expert system application for finding BST recipients is an application based on rules for solving problems to determine BST recipients with a high degree of accuracy and is used as a reference for BST recipients for the government to determine the right target recipients to be selected, and 2) The results of the analysis generated from this system are the same as the results of calculations manually using the theory of the Fuzzy Tsukamoto method so that the accuracy of the results is appropriate with calculations obtained from the trial.